PROBLEM-BASED LEARNING WITH A SCIENTIFIC APPROACH AS A SOLUTION TO DEVELOP STUDENTS' MATHEMATICS LEARNING OUTCOMES - A. Riska Atika; Ridwan Idris; Andi Ika Prasasti Abrar; Ahmad Farham Majid (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This study aims to understand the influence of the problem-based learning model with a scientific approach to grade VIII students' mathematics learning outcomes at SMP Negeri 1 Sungguminasa. This research uses a quasi-experimental method with a non-equivalent control group design. This research collected its research data through the distribution of observation sheets and learning achievement tests. Based on the descriptive statistical analysis results that the average value of student learning outcomes by using the problem-based learning model is 78.7, and the standard deviation is 7.21, while the average value of student learning outcomes without the problem-based learning model treatment is 72.19, and the standard deviation is 7.01. The results of the inferential analysis indicate the significant value (2-tailed) of 0.003 < 0.05, signifying a rejected H0. For that reason, this research concludes that there is a significant difference in grade VIII students' mathematics learning outcomes at SMP Negeri 1 Sungguminasa when the problem-based learning model with a scientific approach is implemented.Abstrak:Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaraan berbasis masalah dengan pendekatan saintifik terhadap hasil belajar matematika siswa kelas VIII SMP Negeri 1 Sungguminasa. Jenis penelitian yang digunakan adalah quasi eksperimen dengan desain penelitian non equivalent control group design. Instrumen yang digunakan adalah lembar observasi dan tes hasil belajar. Berdasarkan hasil analisis deskriptif menunjukkan bahwa nilai rata-rata hasil belajar siswa menggunakan model problem based learning adalah sebesar 78,7 dan standar deviasinya 7,21, sedangkan rata-rata hasil belajar siswa yang tidak menggunakan model problem based learning adalah 72,19 dan standar deviasinya 7,01. Hasil analisis inferensial menunjukkan nilai signifikan (2-tailed) sebesar 0,003 < 0,05, yang berarti H0 ditolak. Oleh karena itu, apat disimpulkan bahwa terdapat perbedaan dalam hasil belajar matematika siswa kelas VIII di SMP Negeri 1 Sungguminasa ketika menerapkan model pembelajaran berbasis masalah dengan pendekatan saintifik.